2012
DOI: 10.1007/s10803-012-1525-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Parent–Child Social Informant Discrepancy in Youth with High Functioning Autism Spectrum Disorders

Abstract: We investigated discrepancies between parent- and self-reported social functioning among youth with autism spectrum disorders (ASD). Three distinct samples showed discrepancies indicating that parents viewed their children as performing one standard deviation below a standardization mean, while youth viewed themselves as comparably-skilled relative to peers. Discrepancies predicted lower parental self-efficacy, and lower youth-reported hostile attributions to peers, marginally-lower depression, and decreased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 53 publications
11
72
0
Order By: Relevance
“…A growing number of studies have addressed the important problem of parentchild reporting discrepancies in high functioning children and adolescents with ASD (e.g., Johnson et al 2009;Lerner et al 2012;Ozsivadjian et al 2014;Sterling et al 2015;Vickerstaff et al 2007), and their results have been mixed. Given that it is highly plausible that reduced selfawareness of one's own social impairments within the ASD population leads to underreporting of anxiety symptoms relevant to social contexts, as might be measured by Social Anxiety or Harm Avoidance scales, it is not surprising that several studies have found parent-child discrepancies in reports of social functioning impairments, with parents reporting poorer functioning (Johnson et al 2009;Lerner et al 2012;McMahon and Solomon 2015;Vickerstaff et al 2007). However, a recent meta-analysis examining agreement in children with ASD and those with intellectual disability found moderate levels of agreement between parents and children for internalizing symptoms (Stratis and Lecavalier 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have addressed the important problem of parentchild reporting discrepancies in high functioning children and adolescents with ASD (e.g., Johnson et al 2009;Lerner et al 2012;Ozsivadjian et al 2014;Sterling et al 2015;Vickerstaff et al 2007), and their results have been mixed. Given that it is highly plausible that reduced selfawareness of one's own social impairments within the ASD population leads to underreporting of anxiety symptoms relevant to social contexts, as might be measured by Social Anxiety or Harm Avoidance scales, it is not surprising that several studies have found parent-child discrepancies in reports of social functioning impairments, with parents reporting poorer functioning (Johnson et al 2009;Lerner et al 2012;McMahon and Solomon 2015;Vickerstaff et al 2007). However, a recent meta-analysis examining agreement in children with ASD and those with intellectual disability found moderate levels of agreement between parents and children for internalizing symptoms (Stratis and Lecavalier 2015).…”
Section: Discussionmentioning
confidence: 99%
“…14 16 Sometimes, there may be disagreement between parent and child reports. 17 It is therefore important for clinicians to collect collateral information from school staff and other caregivers in the form of narratives and behavior reports to supplement their findings.…”
Section: Recommendation 1: Perform a Developmentally Appropriate Multmentioning
confidence: 99%
“…Relations between observed behavior and neural activity may also be non-linear in autism (e.g., “U” shaped) with individuals who are low or high in both clinical features (e.g., self-awareness) and comorbidities (e.g., anxiety) showing different patterns (e.g., Lerner, Calhoun, Mikami, & De Los Reyes, 2012; Pugliese, White, White, & Ollendick, 2013). These examples highlight the need to examine EEG responses in light of other (behavioral) phenotypes and within the profile of autism.…”
Section: Diagnosis and Definition Of Participantsmentioning
confidence: 99%